Power Transformer Diagnostics, Monitoring and Design Features - Issouf Fofana, Ph.D. ing. Chairholder (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Power transformers are key components in electric power distribution and transmission systems, and it is essential that they function properly for many years. With increasing age, there are potential risks of extremely high monetary losses due to unexpected failures and outages. A simple solution would be to replace all aging and risky transformers at once with new ones. Such an approach is obviously not a fiscally realistic solution. The main objectives are to extend their service life and optimize their performance through increased availability. For these reasons, in the past decades transformer life management has gained an ever-increasing interest. The greatest challenges are related to the need for methods to assess their condition and life expectancy along with the improvement of transformers' efficiency by noble designs and/or the application of new materials. This book covers some theoretical and practical developments with special emphasis on R&D trends in transformer diagnostics and monitoring. Graduate-level students and academics as well as scientists and engineers involved in power equipment design, diagnostics, and monitoring will benefit from this book.